CEO Compensation and Firm Performance: The Role of ESG Transparency - Chetna Rath; Florentina Kurniasari; Malabika Deo (Universitas Pasundan, 2020)
Chief executive officers (CEOs) of environmental, social, and governance (ESG) firms are known to take lesser pay and engage themselves in corporate social responsibility activities to achieve the dual objective of the enhancement of firm’s performance as well as benefit for stakeholders in the long run. This study examines the role of ESG transparency in strengthening the impact of firm performance on total CEO pay in ESG firms. A panel of 67 firms for the period of 2014–2019 has been analyzed using the two-step system GMM model, with NSE Nifty 100 ESG Index as the data sample and ESG scores from Bloomberg database as a proxy for transparency. Findings reveal that environmental and governance disclosure scores have the potential to intensify the negative relationship between firm performance and CEO compensation, while social disclosure scores do not. In addition, various firm-specific, board-specific, and CEO-specific attributes have also been considered controls affecting remuneration. This paper contributes to the literature by exploring the effect of exhibiting ESG transparency and its nexus with CEO pay as well as firm performance.